Neural stem cell relay from B1 to B2 cells in the adult mouse ventricular-subventricular zone - Arantxa Cebrian-Silla; Marcos Assis Nascimento; Walter Mancia; Susana Gonzalez-Granero; Ricardo Romero-Rodriguez; Kirsten Obernier; David M. Steffen; Daniel.A. Lim; Jose Manuel Garcia-Verdugo; Arturo Alvarez-Buylla (Cell Reports)
Summary: Neurogenesis and gliogenesis continue in the ventricular-subventricular zone (V-SVZ) of the adult rodent brain. V-SVZ astroglial cells with apical contact with the ventricle (B1 cells) function as neural stem cells (NSCs). B1 cells sharply decline during early postnatal life; in contrast, neurogenesis decreases at a slower rate. Here, we show that a second population of astroglia (B2 cells) that do not contact the ventricle also function as NSCs in the adult mouse brain. B2 cell numbers increase postnatally, are sustained in adults, and decrease with aging. We reveal the transcriptomic profile of B1 and B2 cells and show that, like B1 cells, B2 cells can be quiescent or activated. Transplantation and lineage tracing of B2 cells demonstrate their function as primary progenitors for adult neurogenesis. This study reveals that NSC function is progressively relayed from B1 to B2 progenitors helping explain how neurogenesis is maintained into adult life.